The Impact Of M-Banking On The Satisfaction Of Using Bank Syariah Indonesia With Financial Literacy As A Moderating Variable - Siti Chaniffiya Al Chanafi; Adha, Mufti Alam; Faiza Husnayeni Nahar (JPS (Jurnal Perbankan Syariah), 2025)
Purpose - This study focuses on exploring how m-Banking usage, brand image, and customer protection contribute to customer satisfaction at Bank Syariah Indonesia (BSI), with financial literacy acting as a moderating variable. Islamic mobile banking in Indonesia has seen significant growth over the past decade, reflecting the country’s sizeable Muslim population and increasing demand for Sharia-compliant financial services. Account balance and transaction monitoring; Bill payments and fund transfers; Digital zakat, infaq, and sadaqah payments; Investment in Sharia mutual funds or sukuk (Islamic bonds); QRIS-based payments and e-wallet integration. Using a quantitative approach, this study surveyed to gather primary data through questionnaires distributed to the people in Magelang Regency. Method - This research sampled 100 respondents, chosen through non-probability sampling techniques, specifically targeting customers of Bank Syariah Indonesia. This study analyzed the data using the Partial Least Squares (PLS)-based Structural Equation Modeling (SEM) method. Findings - The results show that m-Banking usage, brand image, and customer protection significantly and positively affect customer satisfaction at Bank Syariah Indonesia. Interestingly, financial literacy does not serve as a moderating variable in the relationship between these three independent factors and customer satisfaction. Implications - These insights highlight the importance of enhancing m-Banking services, reinforcing brand image, and safeguarding customer rights as vital components in fostering customer satisfaction at Islamic banks.